Informal food systems in food security planning: a case study of Nanjing, China - Luoman Zhao; Axel Timpe; Frank Lohrberg (Food Security, 2025)
Continuing risks, such as economic crises, climate change, and pandemics, have raised concerns about food issues in China and worldwide. The current food planning in China, which prioritizes food security, ignores the role of the informal sector in the resilience of food systems. This study examined the role of informal food systems in enhancing food security and explored the dilemmas of informal food systems in food planning through field and literature research. Taking Nanjing as an example, individual and city-level case studies collected data through face-to-face interviews, questionnaires, observations, and secondary data sources. The data were analyzed from three perspectives: food availability, accessibility, and utilization. The results indicated that small-scale food production and food vending contribute to food diversity, affordability, allocation, and nutritional and social value. Face-to-face direct marketing and cheap prices of local food increase the competitiveness of food in informal food systems. Informal food activities still have the potential to be improved by integrating into food security planning. Food security planning should consider the contributions of informal food systems and improve the current situation by appreciating small-scale agriculture, supporting local food supply chains, and providing a formalization procedure for food bottom-up food activities.
Keywords: 630; Informal food systems; Food security; Food planning; Small-scale agriculture; Food vendors